A preliminary study of environmental noise in public university - Haron, Zaiton (Penerbit UTM Press, 2015)
Environmental noise problems have increased every year and have brought negative effects to the neighbouring communities. Educational areas, such as university, college and school, are the places for learning and gaining knowledge. However, students feel stressed and annoyed when they are exposed to noisy environments. The main objective of this research is to investigate the current environmental noise problem in Universiti Teknologi Malaysia (UTM). It is a preliminary study of environmental noise problem and a total of 24 measurement locations were selected based on the working zones in UTM. Each location was measured in an hour during the working period. About 95.8 percent of the measurement results exceeded the permissible limit of the guideline by the Department of Environment (DOE). Besides, the UTM noise zones have been established by referring to the measurement results. The findings of this study could assist the UTM management in deciding the noise abatement strategy. Also, the noise zones could be disseminated to the public in order to increase the public awareness towards the environmental noise problems in UTM.